Perspectives on Adolescent Pregnancy Prevention Strategies in the United States: Looking Back, Looking Forward [Corrigendum] - Brindis CD; Decker MJ; Gutmann-Gonzalez A; Berglas NF (Dove Medical Press, 2022)
Brindis CD, Decker MJ, Gutmann-Gonzalez A, Berglas NF. Adolesc Health Med Ther. 2020;10:135–145. Page 142, Recommendation 5: Design Programs and Services That Recognize and Address Structural Racism, Health Equity, and Inclusion, line four, the text “racism have been fully” should read “racism have not been fully”. The authors apologize for this error.